1991
DOI: 10.4141/cjas91-128
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinology of nutritional flushing in gilts

Abstract: As part of a nutritional flushing study, the endocrine status of gilts was compared to gain further knowledge of the mechanism(s) that mediate the restoration of ovulation rate. From a5.3 kg BW to puberty,42 grlts were fed 2.0 kg d-' (L) d'une fr6quence accrue des d6charges 6pisodiques de pLH. En outre, les truies HH accusaient des concentrations plasmatiques d'insuline sup6rieures (P < 0.05) )r celles des truies LL tout au long de la p6riode p6ri-oestrale, et leurs concentrations en IGF-I 6taient plus 6lev6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0
7

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 22 publications
3
19
0
7
Order By: Relevance
“…Meikle and Drickamer (1986) did not find that premating females had higher fertility or fecundity (litter size). Increased food availability is usually associated with greater fertility and fecundity (Bronson, 1989), but reduced food intake, followed by abundant food just before mating is often used to increase fertility and fecundity in the production of some domestic animals (Beltranena et al, 1991 (Labov et al, 1986). The relatively low mass of adult males born to food-deprived mothers reduces the probability that they will establish and maintain a territory (Vessey, 1967;Krackow, 1993), and they may therefore have rela¬ tively low reproductive potential (Wolff, 1985).…”
Section: Animalsmentioning
confidence: 99%
“…Meikle and Drickamer (1986) did not find that premating females had higher fertility or fecundity (litter size). Increased food availability is usually associated with greater fertility and fecundity (Bronson, 1989), but reduced food intake, followed by abundant food just before mating is often used to increase fertility and fecundity in the production of some domestic animals (Beltranena et al, 1991 (Labov et al, 1986). The relatively low mass of adult males born to food-deprived mothers reduces the probability that they will establish and maintain a territory (Vessey, 1967;Krackow, 1993), and they may therefore have rela¬ tively low reproductive potential (Wolff, 1985).…”
Section: Animalsmentioning
confidence: 99%
“…Previous studies with sheep [22] and mink [17] [34] and pigs [5]. Blood glucose is the primary energy substrate used at the cellular level, and reduced concentrations may influence body composition [26].…”
mentioning
confidence: 99%
“…Flushing has shown positive effects on reproductive performance in different species (gilt: Flowers et al [18]; Beltranena et al [5]; ewe: Haresign [21] and mink: review by Tauson [29]), and because of responsiveness to nutritional changes, it has been hypothesized that some metabolic factors may provide the links between nutrition and reproduction [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Kirkwood et al (1989b) reported that, despite a30% depression in feed intake, pST-injected gilts (90 pg kg-'for 9 d) had ovulation rates comparable to those of vehicle-injected gilts. This observation is of interest because daily injections of insulin (Cox et al 1987) and shortterm increases in feeding level during the first estrous cycle (Beltranena et al 1991) have been shown to increase ovulation rate in gilts. However, the mechanism by which ovulation rate is sustained in pST-treated gilts, despite the depression in feed intake, has yet to be clarifred.…”
Section: Discussionmentioning
confidence: 99%